Pengaruh Financial Leverage Terhadap Kinerja Keuangan (Studi Pada Perusahaan Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2011-2015) - Nopitasari, Hana; Tiorida, Ermina; Sarah, Ira Siti (Jurnal Riset Bisnis dan Investasi, 2017)
The main objective of this study is to determine the effect of financial leverage on financial performance of the 39 selected property and real estate companies listed in Indonesia Stock Exchange over a period of five years (2011-2015). This work employed two financial leverage for the independent variables such as: debt ratio (DR) and debt to equity ratio (DER) in determining their effect on financial performance such as return on equity (ROE), sales growth and price earning ratio (PER) as a dependent variable. The secondary data were obtained from the financial statement (comprehensive income statement and statement of financial position) of the selected companies quoted from the Indonesia Stock Exchange (IDX). Descriptive statistical test, simple linear regression test and hypothesis test are used to analyze the data of this research. The results of the analysis show that there is a positive and insignificant influence between financial leverage on the financial performance of 39 companies, proven by hypothesis testing of t-value (1.610) < t-table (1.65481) and P-value of 0.109, while the value of regression coefficient of financial performance of 0.008.